2021
DOI: 10.3390/nu13114096
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Symptoms and Well-Being in Overweight and Underweight Adolescents: A Network Analysis

Abstract: Overweight and underweight adolescents have an increased risk of psychological problems and reduced quality of life. We used a network analysis approach on a variety of psychopathology and well-being variables to identify central factors in these populations. The network analysis was conducted on data of 344 overweight adolescents (>90th BMI-percentile) and 423 underweight adolescents (<10th BMI-percentile) drawn from a large community sample (10–19 years) including behavioral and emotional problems (You… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 62 publications
0
11
0
1
Order By: Relevance
“…According to previous studies [7], young patients with AN reported that they had lost their daily life structure, especially during school closures [32]; according to Zeiler et al [7] they complained of participating in fewer outdoor activities, including sports, during the lockdowns, which then triggered weight phobia. In addition, they had more spare time and experienced more boredom, which led to increased activity in social media, especially on websites glorifying slimness and a well-trained body [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies [7], young patients with AN reported that they had lost their daily life structure, especially during school closures [32]; according to Zeiler et al [7] they complained of participating in fewer outdoor activities, including sports, during the lockdowns, which then triggered weight phobia. In addition, they had more spare time and experienced more boredom, which led to increased activity in social media, especially on websites glorifying slimness and a well-trained body [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a small Austrian study, adolescents with AN reported reduced motivation to work on recovery, as well as increased exposure to triggering stimuli by media and social media and a disruption of treatment routines, which were all shown to interfere with the improvement of health [7]. Additionally, adolescents who were referred to a tertiary eating disorder care program in Canada were significantly more medically unstable, required significantly more hospitalizations, and showed higher rates of self-reported impairment than patients who were referred one year previous [8].…”
Section: Introductionmentioning
confidence: 99%
“…These aforementioned findings remain serious and are not spurious as indicated by a recent systematic review of 11 studies involving multiple almost 70.000 youth conducted by Rao et al 9 As such, and implied by Rao et al, 10 those at risk for depression, as well as those found to be depressed need careful ongoing attention. Alternately, as outlined by Zeller et al, 11 obesity in childhood and adolescence will surely tend to remain a global health challenge of immense proportion and increasing poor health outcomes if timely efforts to address this issue continue to focus largely on eating and physical activity practices to the exclusion of the role of the contribution of multiple mental health attributes on the emergence of obesity and overall future wellbeing of the overweight child. 12…”
Section: Overviewmentioning
confidence: 99%
“…14,15 Moreover, the study reported that psychological problems was also increased in underweight adolescents. 16 Thus, this study compared the levels of physical activity, cognitive function and depression among Thai adolescences who were underweight, normal weight, overweight and obese. In this study, the measurement outcomes including physical activity components, cognitive performance, and depression severity were measured in all groups.…”
Section: Participantsmentioning
confidence: 99%
“…Total scores ranging from 0 to 27 are used to self-screen for primary depression during the previous 2 weeks. The PHQ-A scores can be classified as minimal (PHQ-A scores ≤4), mild (PHQ-A scores 5-9), moderate (PHQ-A scores 10-14), moderately severe (PHQ-A scores [15][16][17][18][19] and severe depression (PHQ-A scores 20-27). 26…”
Section: Assessment Of Depressionmentioning
confidence: 99%